Recurrence Risk of Febrile Seizures in Children - Agrawal, Jyoti; Poudel, Prakash; Shah, Gauri S; Yadav, Satish; Chaudhary, Shipra; Kafle, Shyam (Journal of Nepal Health Research Council, 2017)
Background: Identifying children with febrile seizure who are at risk for recurrence is important so that special attention can be given to them. The objective of this study was to identify the risk factors for recurrence of febrile seizures in children. Methods: This prospective hospital based study was conducted from July 2013 to August 2014 ‘among children of 6 months to 6 years of age at Bishweshwar Prasad Koirala Institute of Health Sciences (BPKIHS), Nepal. Children meeting the selection criteria were enrolled in study. Clinical, investigation, treatment and outcome parameters were analyzed. Results: A total of 92 children with febrile seizure were enrolled in study. Males accounted for 70% and females 30%. Simple febrile seizure was present in 48% and complex febrile seizures were seen in 52%. Recurrence of seizure was seen in one third of cases. Loss of consciousness was most common post-ictal phenomenon followed by confusion and lethargy. Upper respiratory infection was the most common precipitating factor. Generalized Tonic Clonic Seizure was the most common seizure type present in 79% of cases. Significant risk factors for recurrence occurred in males (p=0.088), age less than 1 year (p=0.003). Most of the recurrence occurred within one year of first seizure. Conclusions: Febrile Seizure is common in males. Almost one third of children with febrile seizure are at risk for recurrence. The significant risk factors for recurrences are male gender and age <1year. Keywords: Epilepsy; febrile seizure; recurrence